2014
DOI: 10.1542/peds.2012-1372
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Fever in MVK Deficiency: A Patient Initially Diagnosed With Incomplete Kawasaki Disease

Abstract: Mevalonate kinase deficiency (MKD) is a rare autosomal recessive disorder causing 1 of 2 phenotypes, hyperimmunoglobulin D syndrome and mevalonic aciduria, presenting with recurrent fever episodes, often starting in infancy, and sometimes evoked by stress or vaccinations. This autoinflammatory disease is caused by mutations encoding the mevalonate kinase (MVK) gene and is classified in the group of periodic fever syndromes. There is often a considerable delay in the diagnosis among pediatric patients with recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
11
1
Order By: Relevance
“…The case presents the recurrence of fever after diagnosed Kawasaki disease with coronary artery involvement. 8 The basic difference with our case is that the first attack of the patient occurred at the age of 4, and the fever repeated 1 year later. In this condition, findings did not comply with the characteristics of hyperimmunoglobulin D syndrome, which are almost always seen in infancy, and the fever repeated every 4-6 weeks.…”
Section: Discussioncontrasting
confidence: 64%
“…The case presents the recurrence of fever after diagnosed Kawasaki disease with coronary artery involvement. 8 The basic difference with our case is that the first attack of the patient occurred at the age of 4, and the fever repeated 1 year later. In this condition, findings did not comply with the characteristics of hyperimmunoglobulin D syndrome, which are almost always seen in infancy, and the fever repeated every 4-6 weeks.…”
Section: Discussioncontrasting
confidence: 64%
“…We have previously reported the clinical presentation of systemic onset juvenile arthritis after the KD diagnosis and noted on literature review of prior reported cases that most were diagnosed as incomplete KD specifically lacking scleral injection [4]. Mevalonate kinase deficiency and PFAPA diagnoses causing recurrent fevers have been previously described after initial treatment for incomplete KD [10,11]. Whether children who were subsequently diagnosed with an autoimmune/autoinflammatory illness actually had KD initially or had an alternative diagnosis is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient had findings suggesting incomplete KD, urinary tract infection (UTI), and appendicitis, but these alternative diagnoses can be reconciled with the diagnosis of TRAPS. Transient coronary arteritis has been reported to occur in other autoinflammatory diseases [11, 12, 13]. Furthermore, the development of distinct autoinflammatory syndromes in patients with a history of KD has also been described [14] and it has been postulated that such immune dysregulation may also predispose patients to KD.…”
Section: Discussionmentioning
confidence: 99%